An Examination of Parental and Peer Influence on Substance Use and Criminal Offending During the Transition From Adolescence to Adulthood. (June 2018) - Beardslee, Jordan; Datta, Sachiko; Byrd, Amy; Meier, Madeline; Prins, Seth; Cerda, Magdalena; Pardini, Dustin
Although peer behavior and parent–child conflict have been associated with adolescent and young adults' behavior, prior studies have not adequately controlled for selection effects and other confounders, or examined whether associations change across the transition to adulthood or by race. Using annual data from men followed from age 17 to 26, within-individual change models examined whether substance use or offending increased in the year after boys began affiliating with friends who engaged in substance use/offending and/or experienced increased parent–son conflict. Moderation analyses tested whether associations varied by age or race. Alcohol use, marijuana use, and offending (Black participants only) increased in the year after boys began affiliating with more peers who engaged in similar behaviors. Associations were strongest during adolescence for substance use. Parent–son conflict was not associated with the outcomes. Findings underscore the importance of developmental and racialized differences in understanding the role of social influences on young men's substance use and offending.